INDONESIA IN THE GLOBALIZATION TRAP: A HISTORICAL PERSPECTIVE - Sulistiyono, Singgih Tri (Paramita: Historical Studies Journal, 2017)
By using historical approach, this article intends to examine the problems faced by Indonesia as a developing country in connection to the strengthening process of globalization. The rapid process of globalization has been responded aggresively by Indonesia without considering internal readiness. Since the New Order period, Indonesia has been very eager to appear as a modern nation by coping with the demand of globalization and economic liberalization as has been campaigning by the developed countries. Indonesia has responded excessively to liberalization through the jargon of globalization and regionalization. That is, Indonesia is very open to free competition with the outside world while the internal condition has not been well prepared. Internal conditions include the bureaucracy and other institutions as well as the quality of human resources. Since the New Order government, dozens of bilateral, multilateral, and international agreements have been signed by the Indonesian government for performing economic liberalization in the field of investment, trade, and labor which in turn causing what the so called ‘globalization trap’. Dengan menggunakan pendekatan historis, artikel ini bermaksud untuk meneliti masalah yang dihadapi oleh Indonesia sebagai negara berkembang sehubungan dengan proses    penguatan globalisasi. Proses cepat globalisasi telah direspon agresif oleh Indonesia tanpa mempertimbangkan kesiapan internal. Sejak masa Orde Baru, Indonesia sudah sang-at bersemangat untuk tampil sebagai bangsa modern dengan mengatasi permintaan globalisasi dan liberalisasi ekonomi seperti telah berkampanye oleh negara-negara maju. Indonesia telah menanggapi secara berlebihan liberalisasi melalui jargon globalisasi dan regionalisasi. Artinya, Indonesia sangat terbuka untuk persaingan bebas dengan dunia luar sementara kondisi internal belum siap. Kondisi internal meliputi birokrasi dan lembaga lainnya serta kualitas sumber daya manusia. Sejak pemerintah Orde Baru, puluhan perjanjian bilateral, multilateral, dan internasional telah ditandatangani oleh pemerintah Indonesia untuk melakukan liberalisasi ekonomi di bidang investasi, perdagangan, dan tenaga kerja yang pada gilirannya menyebabkan apa yang disebut 'globalisasi perangkap'.